Ethernet-based AFDX simulation and time delay analysis - Feng, Tao (Cranfield University, 2016)
Nowadays, new civilian aircraft have applied new technology and the amount of embedded systems and functions raised. Traditional avionics data buses design can‘t meet the new transmission requirements regarding weight and complexity due to the number of needed buses. On the other hand, Avionics Full Duplex Switched Ethernet (AFDX) with sufficient bandwidth and guaranteed services is considered as the next generation of avionics data bus. One of the important issues in Avionics Full Duplex Switched Ethernet is to ensure the data total time delay to meet the requirements of the safety-critical systems on aircraft such as flight control system. This research aims at developing an AFDX time delay model which can be used to analyse the total time delay of the AFDX network. By applying network calculus approach, both (σ,ρ) model and Generic Cell Rate Algorithm (GCRA) model are introduced. For tighter time-delay result, GCRA model is applied. Meanwhile, the current AFDX network simulation platform, FACADE, will be enhanced by adding new functions. Moreover, avionics application simulation modules are developed to exchange data with FACADE. The total time delay analysis will be performed on the improved FACADE to validate this AFDX network simulation platform in several scenarios. Moreover, each scenario is appropriated to study the association between total time delay performance and individual variable. The results from updated FACADE reflect the correlation between total time delay and certain variables. Larger BAG and more switches between source and destination end systems introduce larger total time delay while Lmax could also affect the total time delay. However, the results illustrate that the total time delays from updated FACADE are much larger than GCRA time delay model which could up to 10 times which indicates that this updated FACADE needs further improvement.
Keywords: Avionics Full-Duplex Switched Ethernet; Network Calculus; Arrival Curve; Service Curve; GCRA; Total Time Delay